Policy Evaluation of Determining Asset Quality on Credit Quality at PT. XYZ (National Economic Stimulus Program) - Shinta Chandra Rahmawati (PT Mattawang Mediatama Solution, 2023)
Banks in implementing policies that support economic growth stimulus still pay attention to the application of risk management as stipulated in the Financial Services Authority regulations regarding the application of bank risk management. PT. XYZ is a state-owned company engaged in conventional general banking services. One part that directly impacts this pandemic is the Credit Unit. The impact of PPKM so far has significantly affected business decline. Therefore verification and cleansing of newspaper accounts as well as performing a more thorough analysis of the debtor's finances. So far it hasn't arrived downgrade and is still well guarded even with the restructuring lane. The business prospects and debtor's repayment capacity tend to decrease and the repayment capacity has limited the policy for determining the quality of fixed assets is the same as before, at least 110% of the maximum credit that has been set. For the general trading business sector, it can still be considered prospective, supported by marketability and strategic assets so that debtors are considered capable of carrying out their responsibilities towards their obligations to the bank.